Prediction of grinding force for brittle materials considering co-existing of ductility and brittleness. Issue 5 (November 2016) - Wu, Chongjun; Li, Beizhi; Yang, Jianguo; Liang, Steven
Abstract Grinding of brittle materials is characterized by a complex removal mechanism of both ductile and brittle removal. Therefore, the traditional force models, which are mainly targeted to metallic materials, cannot be fully applied to the force prediction of brittle materials. This paper will propose a new grinding force model for brittle materials considering co-existing of ductile removal force and brittle removal force. The ductile removal force is mainly composed of rubbing force, ploughing force, and chipping force. However, the brittle removal force is more related to rubbing force and fracture chipping force. The proportional coefficient of ductile removal and crack size will be modeled through a series of experiments under different wheel speed and undeformed chip thickness. The working status for a single grit was separated based on the Hertz Theory and chip thickness modeling of Rayleigh probability density function. Grinding experiments have been undertaken by using a high speed diamond grinder on Silicon Carbide, and the results was compared to the force model predictions for validation. The predictive force model shows a reasonable agreement quantitatively with the experimental force data.